Polymer-supported Lewis acids and bases: Synthesis and applications. (December 2020) - Yolsal, Utku; Horton, Thomas A.R.; Wang, Meng; Shaver, Michael P.
Abstract: In the past decade the synthesis of novel stimuli-responsive materials has been driven by the pursuit of new applications and, more recently, sustainable and reusable systems. Of these materials, those which incorporate main group Lewis acids (LAs) and bases (LBs) into their polymer backbones have shown extraordinary utility as a result of their synthetic diversity, enabling fine tuning of reactivity and ensuing properties tailored to the desired application. Herein, the recent progress made in the synthesis and applications of macromolecular LAs and LBs is being highlighted. Interactions between polymeric LAs and LBs can be exploited to build supramolecular polymeric networks based on both conventional and frustrated Lewis pairs, while using either functionality individually enables the preparation of sensors for anions, cations, explosives and biological molecules. The presence of polymer-supported LAs/LBs in organocatalysis has been extended to controlling polymer morphology, enabled improvements in activity through compartmentalization and the coexistence of classically incompatible functionalities. Finally, the versatility of this field is being demonstrated by highlighting some of the recent advances in CO2 chemisorption systems employing amine-based polymeric LBs for carbon capture and reduction. Graphical abstract: Image, graphical abstract